The influence of Fe doped TiO2 as inorganic additive on the properties of polysulfone ultrafitration membrane - Syamsutajri, Syamsol Bahri; Zawati, Harun; Wan Norhayati, Wan Salleh; Muhammad Nur Hakim, Abd Kadir; Norazlianie, Sazali; Rosniza, Hussin; Hatijah, Basri (UTM Press, 2019)
Recent development of utrafiltration (UF) technology for the mixed matrix polymeric membranes plays an important role to improve membrane properties. In this paper, the effects of inorganic additives prepared by green synthesis route towards polysulfone (PSf) membrane performance at different concentrations of Fe-TiO2 (1.0wt%, 3.0wt% and 5.0wt%) have been investigated. The blended membranes were fabricated via phase inversion using PSf as based polymer, N-metyl-2- pyrrolidone (NMP) as solvent, distilled water as a non-solvent, polyethylene glycol (PEG) as pore performing agent and Fe doped TiO2 nanomaterial as inorganic additive. The characterization and morphology of the polysulfone mixed matrix membranes were analyzed via scanning electron microscopy (SEM), atomic force microscopy (AFM), contact angle and porosity. The performances of the membrane were evaluated in terms of pure water flux (distilled water) and rejection (humic acid) by using membrane permeation testing unit. The results of microscopic images revealed that the membranes incorporated with Fe doped TiO2 have the asymmetric structure while the number and length of finger-like pores at top layer slightly increased from 3.0 wt% to 5.0 wt%, indicating the effect of hydrophilicity. Furthermore, the increasing of Fe-TiO2 percentages also increased the porosity of membrane, as well as rejection percentages and hydrophilicity of membrane.